Diseño y construcción de un sistema USB híbrido para control y monitoreo de procesos industriales bajo entorno gráfico Labview - Amaya Vásquez, Luis Guillermo (2008)
The system hybrid USB of acquisition of data and control is a platform of industrial control the the one which you had fused with the best characteristics and flexibility of a PC and the dependability of a programmable logical controller (PLC) guided toward the control and monitoreo of industrial processes. Reason why the system this constituted of two leaves Software and Hardware The software for the development of programs of acquisition of data control and monitoreo, will be carried out on Labview 8.5" (or superior) of National Instruments under the operative systems Windows XP, Windows seen, Mac, Linux. LabView is a suitable language for industrial applications, as the monitoreo of temperatures, speeds, the automation of processes, control of motors and robots, it allows the user to design the program, so that it is able to administer, to process and to execute all the instructions that it contains a program requesting the reading or writing of data. For this reason the system has a bookstore that installs three new subvis in the palette of functions that they allow to carry out acquisition and the control of data and it has a controller USB for the communication for the port USB to a speed of 1.5Mb/s. To the hardware it has denominated it to him TAC-USB (card of acquisition of data and control) that it is insertable through the port USB and they allow the entrance and exit of data from the computer to other apparatuses, where sensors and actuadores are connected, for interactuar with the real world. The data that you/they enter and they leave they can be digital or similar signs, or simply counts of digital occurrences, so much of entrance, as of exit for then to be presented the result in the screen of the computer in form graph and numeric. Giving the information in such a way that any person can interpret easily as a result. Eight channels of digital entrances, six channels of entrances similar to 10 bits and an earth are distributed in a single bus of 15 screw connectors that you/they allow a quick and firm interconnection of sensors and systems of signals. The same as the entrances, the 8 digital channels of exit to relé and the exit channel to PWM by means of a relé of solid state are distributed in a single bus of 9 screw connectors that you/they facilitate the one it couples allowing to control external systems as makers, switches, and other teams guided toward applications in the industry the home and in investigation activities.